ASILUM HAK CIPTA MUSIK YANG DIKOMERSILKAN TANPA HAK OLEH BISNIS KARAOKE - Dena Trysa Aulia; Rakhmita Desmayanti (Fakultas Hukum Universitas Trisakti, 2022)
The case is about Rasa Sayang Karaoke Business Outlet Veranza/Broadway Surabaya which launches music broadcasts without permission from the creators/owners, copyright holders and without paying any royalties. For this reason, the author will conduct a research on how the asylum of copyright law arrangements for musical works that are used without rights by the Karaoke business of Rasa Sayang Surabaya based on Law number 28 of 2014 Concerning Copyright and what is the role of LMK in distributing royalties to creators whose songs are broadcast without rights by the karaoke business outlet Rasa Sayang Surabaya. The research conducted by the authors is normative and descriptive analytical legal research, using secondary data with primary data as supporting data and the conclusions are drawn using deductive method. The legal basis for the copyright of music works that are used without rights by the karaoke business is based on “Article 113 of Law No. 28 of 2014 concerning Copyright